Evaluation of the usability, accessibility and acceptability for a family support intervention (Family-Focused Support Conversation) for end of life care discharge planning from hospital: A participatory learning and action research study. (November 2021) - Duke, Sue; Richardson, Alison; May, Carl; Lund, Susi; Lunt, Neil; Campling, Natasha
Abstract: Background: Family support is internationally recognised as integral to palliative care. However, during end of life care discharge planning from hospital, families report a lack of opportunity to discuss their concerns or contribute their knowledge of the ill family member and consequently feel unheard and unsupported. To counter this experience, we co-produced the Family-Focused Support Conversation, a novel research-informed intervention, to guide discussion of family concerns about the meaning, implications and manageability of end of life caregiving following discharge. Objectives: To qualitatively evaluate the usability, accessibility and acceptability of the Family-Focused Support Conversation in hospital and factors which promote and inhibit implementation. Design: Participatory Learning and Action Research design, guided by Normalization Process Theory, a social implementation theory. Settings: Implementation was undertaken by 45 clinical co-researchers, specialist nurses ( n =42) and occupational therapists ( n =3), working in specialist palliative care teams in twelve hospitals (within seven NHS Trusts) across England, over a six-month period. Methods: During implementation clinical co-researchers collected reflective data about intervention delivery ( n =110), participated in regular in-depth conversations of implementation with the research team ( n =26 meeting records) and in a final evaluation meeting ( n =11 meeting records). Data from family members who had received the intervention, comprised brief questionnaires ( n =15) and in-depth semi-structured interviews ( n =6). Data were qualitatively analysed, informed by Normalization Process Theory and Family Sense of Coherence Theory. Results: Clinical co-researchers found the intervention eminently usable and accessible. They reported a shift in family support from informing family members about patient healthcare needs, to family concerns such as how they made sense of the meaning of discharge, and how to provide family-orientated care. Family members found the intervention acceptable, they felt supported and able to make informed decisions about their role in providing end of life care. Implementation was positively influenced by coherence between the intervention and value placed on family care by clinical co-researchers. Once incorporated in their practice intervention delivery took no longer than usual practice and could be divided across consultations and collectively delivered with ward and discharge teams. Conclusions: The Family-Focused Support Conversation is usable, accessible and acceptable. It enhances family support by facilitating discussion of family concerns about end of life caregiving and results in family members making informed decisions about their role in end of life care following discharge. Trial registration: n/a.